2010
DOI: 10.1111/j.1365-2672.2010.04809.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial activity and community structure in a lake sediment used for psychrophilic anaerobic wastewater treatment

Abstract: Aims:  The aim of the study was to investigate the feasibility of a continuous reactor for psychrophilic anaerobic wastewater treatment by using the sludge from cold natural environment. Methods and Results:  Six sludge samples (S1–S6) were collected from different cold natural locations to select sludge with high anaerobic microbial activity under low temperatures. After a 225‐day incubation, the maximum specific methane production rate of a waterfowl lake sediment (S1) at 15°C (70·5 mLCH4 gVSS−1 day−1) was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(53 reference statements)
0
7
0
2
Order By: Relevance
“…The requirement for a psychrophilic, or psychrotolerant, inoculum for successful LtAD has been proposed as being advantageous. The use of a truly psychrophilic inoculum (from naturally cold environments) has been tested by Xing, Zhao and Zuo ( 2010 ) and Petropoulos et al. ( 2017 ) with promising results.…”
Section: Introductionmentioning
confidence: 99%
“…The requirement for a psychrophilic, or psychrotolerant, inoculum for successful LtAD has been proposed as being advantageous. The use of a truly psychrophilic inoculum (from naturally cold environments) has been tested by Xing, Zhao and Zuo ( 2010 ) and Petropoulos et al. ( 2017 ) with promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al used pig manure as raw material to carry out low‐temperature biogas fermentation at 15°C and found that Methanobacterium formicicum which can convert CO 2 and H 2 into methane in the methanogenesis stage was the most abundant archaeal species. Xing et al fermented algae as raw material at 15°C and found that hydrogen‐consuming Methanomicrobiales and Methanobacteriaceae were dominant. These findings may be related to the ability of hydrogenotrophic methanogens to adapt to a cold environment.…”
Section: Discussionmentioning
confidence: 99%
“…El quitosano tiene acción antimicrobiana en alimentos, se ha descrito su acción in vitro sobre patógenos contaminantes de productos cárnicos y cecinas mencionando entre los principales, Escherichia coli, causante de graves complicaciones como la colitis hemorrágica y el síndrome urémico hemorrágico, y que su mayor fuente de infección son los alimentos de origen animal, principalmente carne de vacuno molida y leche cruda , Escherichia coli (Li et al, 2006;Xing et al, 2009); Staphylococcus aureus (Li et al, 2006); Listeria monocito genes (Li et al, 2006, Valbuena et al, 2012.…”
Section: Figura 2 Aplicaciones Generales Del Polímero Quitosanounclassified